2018
DOI: 10.2147/dnnd.s121099
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Duchenne muscular dystrophy: current findings

Abstract: Numerous biomarkers have been unveiled in the rapidly evolving biomarker discovery field, with an aim to improve the clinical management of disorders. In rare diseases, such as Duchenne muscular dystrophy, this endeavor has created a wealth of knowledge that, if effectively exploited, will benefit affected individuals, with respect to health care, therapy, improved quality of life and increased life expectancy. The most promising findings and molecular biomarkers are inspected in this review, with an aim to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 142 publications
1
44
0
1
Order By: Relevance
“…Some candidate DMD biomarkers have been identified in several studies and species, and their responsiveness to therapies demonstrated, whereas others may have been identified in a single study or show wide variation between individuals and between studies (Table 1 and discussed below). For example, one classic widely used clinical blood ( plasma) biomarker for DMD is the enzyme creatine kinase (CK; Box 1), which is elevated in patients and in rodent and dog DMD models, but can be highly variable (reviewed by Dowling et al, 2019;Hathout et al, 2014;Szigyarto and Spitali, 2018). Nevertheless, increased CK levels, specifically the MM muscle form measured by immunoassay in dried bloodspots, are now being used for newborn DMD screening (Moat et al, 2017).…”
Section: Overview Of Molecular Biomarkers Especially For Myonecrosismentioning
confidence: 99%
See 4 more Smart Citations
“…Some candidate DMD biomarkers have been identified in several studies and species, and their responsiveness to therapies demonstrated, whereas others may have been identified in a single study or show wide variation between individuals and between studies (Table 1 and discussed below). For example, one classic widely used clinical blood ( plasma) biomarker for DMD is the enzyme creatine kinase (CK; Box 1), which is elevated in patients and in rodent and dog DMD models, but can be highly variable (reviewed by Dowling et al, 2019;Hathout et al, 2014;Szigyarto and Spitali, 2018). Nevertheless, increased CK levels, specifically the MM muscle form measured by immunoassay in dried bloodspots, are now being used for newborn DMD screening (Moat et al, 2017).…”
Section: Overview Of Molecular Biomarkers Especially For Myonecrosismentioning
confidence: 99%
“…More recently, extensive proteomic, RNA and metabolite analyses have been carried out in animal models and patients, as discussed in a number of excellent reviews on potential biomarkers for muscle, blood and urine (Aartsma-Rus et al, 2018; Aartsma-Rus and Spitali, 2015;Dowling et al, 2019;Hathout et al, 2014Hathout et al, , 2016Lourbakos et al, 2017;Parolo et al, 2018;Szigyarto and Spitali, 2018;Thangarajh et al, 2019). A large-scale proteomic approach to identify serum biomarkers associated with pathophysiological change over time (Spitali et al, 2018) concluded that ∼33 proteins were bona fide biomarkers as they were able to discriminate between DMD patients and healthy controls in all cohorts, with a concordant directional change towards either a consistent increase or decrease in patients.…”
Section: Overview Of Molecular Biomarkers Especially For Myonecrosismentioning
confidence: 99%
See 3 more Smart Citations